2002
DOI: 10.1111/j.1749-0774.2002.tb00097.x
|View full text |Cite
|
Sign up to set email alerts
|

Combined Use of Hyperthermia and Irradiation Cause Antiproliferative Activity and Cell Death to Human Esophageal Cell Carcinoma Cells-Mainly Cell Cycle Examination

Abstract: In clinically hyperthermia and irradiation therapy for malignant neoplasms are known that they have antiproliferative activity and cell death (including apoptosis) inducing activity. However not only mechanisms of cell death induction but treatment effects of them still have been unclear. In this time we showed that cell cycles from G0/G1 phase to S-G2/M phase were delayed by hyperthermia and G2/M phase accumulation were caused immediately by irradiation. And we also demonstrated that the combination treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…The cell cycle thus appeared to be arrested at the G2/M phase (24). Yuguchi also observed that hyperthermia could arrest the cell cycle at the G0/G1 phase (25). The MTT results showed that Fe 2 O 3 nanoparticle ferrofluid hyperthermia inhibited the proliferation of SMMC-7721 cells.…”
Section: Discussionmentioning
confidence: 98%
“…The cell cycle thus appeared to be arrested at the G2/M phase (24). Yuguchi also observed that hyperthermia could arrest the cell cycle at the G0/G1 phase (25). The MTT results showed that Fe 2 O 3 nanoparticle ferrofluid hyperthermia inhibited the proliferation of SMMC-7721 cells.…”
Section: Discussionmentioning
confidence: 98%
“…Compared with cells in the control group, a hypodiploid peak was seen in the pre-G1 phase in cells of the thermotherapy group, which can induce hysteresis in the G2/M phase of the cell cycle. 22 In summary, in the present study, we successfully prepared Fe 3 O 4 paramagnetic nanoparticles. In vitro heating tests confirmed their good heating ability.…”
Section: Discussionmentioning
confidence: 99%
“…The cells go through G1, S, G2 and M stages in turn during proliferation. It has been reported that the cell cycle is arrested at the G0/G1 phase after hyperthermia 18 . It has been reported by domestic researchers that the tumor cells are arrested at the G1 phase and G2/M phase to a greater or lesser extent after hyperthermia treatment 19,20 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the cell cycle is arrested at the G0/G1 phase after hyperthermia. 18 It has been reported by domestic researchers that the tumor cells are arrested at the G1 phase and G2/M phase to a greater or lesser extent after hyperthermia treatment. 19,20 We used flow cytometry to detect the changes in the cell cycle of Lewis lung cancer cells after hyperthermia treatment.…”
Section: Figurementioning
confidence: 99%